Analisis determinan keputusan nasabah menabung pada Bank Pembangunan Daerah Jambi (Studi kasus pegawai negeri sipil Kota Jambi) - Lilia Sari Putri, Justia; Heriberta, Heriberta; Emilia, Emilia (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine the characteristics of Jambi Regional Development Bank customers and to analyze the determinants of customer decisions to save at the Jambi Regional Development Bank, a case study of civil servants in Jambi City. This study uses data collection techniques through questionnaires distributed online, with a sampling technique that is simple random sampling with quantitative descriptive research methods and analyzed using binary logistic regression models through the SPSS program. The sample is Jambi city civil servants as many as 99 respondents. This study indicates that the variables of income and education have no positive and significant effect on the customer's decision to save. While the civil servant class variables were divided into two using a dummy variable namely, civil servant class III had no significant effect. In contrast, class IV civil servant had a positive and significant impact on customer saving decisions. And the age variable has a positive and significant impact, and the number of family dependents has a negative and significant effect on the customer's decision to save. Â Keywords: Customer decision, Age, Number of dependents